VD_FINDINFO Jug / 2017 / 64 vom 9. März 2007 - VD Tribunal cantonal (2007)
PRÉVENU, ACQUITTEMENT, RÉVISIONDÉCISION, INDEMNITÉEN GÉNÉRAL, FRAIS DE LA PROCÉDURE, DÉPENS | 28 CC, 415 CPP (CH), 426 al. 2 CPP (CH), 429 CPP (CH), 436 al. 4 CPP (CH)